First study on the formation and resuscitation of viable but nonculturable state and beer spoilage capability of Lactobacillus lindneri. (June 2017) - Liu, Junyan; Li, Lin; Li, Bing; Peters, Brian M.; Deng, Yang; Xu, Zhenbo; Shirtliff, Mark E.
Abstract: Objectives: This study aimed to investigate the spoilage capability of Lactobacillus lindneri during the induction and resuscitation of viable but nonculturable (VBNC) state. Methods: L. lindneri strain was identified by sequencing the PCR product (amplifying 16S rRNA gene) using ABI Prism 377 DNA Sequencer. During the VBNC state induction by low temperature storage and beer adaption, total, culturable, and viable cells were assessed by acridine orange direct counting, plate counting, and Live/Dead BacLight bacterial viability kit, respectively. Organic acids and diacetyl concentration were measured by reversed-phase high performance liquid chromatography and head dpace gas chromatography, respectively. Results: VBNC state of L. lindneri was successfully induced by both beer adaption and low temperature storage, and glycerol frozen stock was the optimal way to maintain the VBNC state. Addition of catalase was found to be an effective method for the resuscitation of VBNC L. lindneri cells. Furthermore, spoilage capability remained similar during the induction and resuscitation of VBNC L. lindneri . Conclusions: This is the first report of induction by low temperature storage and resuscitation of VBNC L. lindneri strain, as well as the first identification of spoilage capability of VBNC and resuscitated L. lindneri cells. This study indicated that the potential colonization of L. lindneri strain in brewery environment, formation and resuscitation of VBNC state, as well as maintenance in beer spoilage capability, may be an important risk factor for brewery environment. Highlights: This is the first report of VBNC state induction of L. lindneri strain by low temperature storage. This is the first report of VBNC state resuscitation of L. lindneri strain by addition of catalase. This is the first identification of spoilage capacity of VBNC and resuscitated L. lindneri cells. Glycerol frozen stock is the optimal way to maintain the VBNC state.